2006
DOI: 10.1001/archopht.124.11.1608
|View full text |Cite
|
Sign up to set email alerts
|

Development of Astigmatism and Anisometropia in Preterm Children During the First 10 Years of Life

Abstract: To assess the development of astigmatism and anisometropia to 10 years of age in preterm children, previously included in a population-based study on the incidence of retinopathy of prematurity. Methods: Cycloplegic retinoscopies were performed in 198 preterm children at 6 months, 2 1 ⁄2 years, and 10 years of age. We analyzed the development of astigmatism of 1 diopter (D) or more and anisometropia of 1 D or more. Results: The amount and prevalence of astigmatism declined between 6 months and 2 1 ⁄2 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
2
27
3
1
Order By: Relevance
“…This was also observed in the O'Connor et al (10) study, concerning children with severe ROP, but in the mild ROP group they have found VAs similar to those without ROP. In our study as well as in the Swedish population-based study (11,13,14,16), it could not be determined whether the reduced VA in the treated eyes was due to the treatment or the severe ROP per se. Therefore all eyes corresponding to the criteria for ROP treatment had been treated.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This was also observed in the O'Connor et al (10) study, concerning children with severe ROP, but in the mild ROP group they have found VAs similar to those without ROP. In our study as well as in the Swedish population-based study (11,13,14,16), it could not be determined whether the reduced VA in the treated eyes was due to the treatment or the severe ROP per se. Therefore all eyes corresponding to the criteria for ROP treatment had been treated.…”
Section: Discussioncontrasting
confidence: 59%
“…The present study revealed that the prevalence of astigmatism more than 2D was dominant in the premature group compared with that in the control group, especially the premature treated group had the highest prevalence of astigmatism more than 2D. The Swedish population-based study (11,13,14,16) had confirmed that the stage of ROP and cryotreatment per se were identified as risk factors for astigmatism of 1D. In the Quinn et al (27) study the results showed a tendency for a higher frequency of astigmatism of 1D or more in treated than untreated eyes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The decreases in prevalence of astigmatism were reported as being from 6 to 30 months of corrected age in three previous studies of preterm infants. 3,18,19 Conversely, a recent study, in which 293 children with birth BW o1701 g underwent refractive measurement at 10-12 years, reported little change in astigmatism power or axis, with 75% of children showing an increase in cylinder power within 0.75 D when compared with the measurement at 6 months. 20 Theng et al 21 similarly reported an increase in astigmatism during the first 3 years of life in preterm children.…”
Section: Discussionmentioning
confidence: 93%
“…introducción existe una conocida asociación entre prematurez y mayor frecuencia de presentación de patologías oftalmológicas dentro de las que se incluyen, además de la retinopatía del prematuro (Rop), los vicios de refracción, el estrabismo y la ambliopía [1][2][3][4][5][6] . esta mayor probabilidad de presentar morbilidad oftalmológica sitúa a los niños prematuros en un grupo de especial riesgo que requiere controles clínicos seriados a fin de detectarla y tratarla a tiempo ya que de otro modo puede conducir al desarrollo anormal de la visión, fenómeno conocido como ambliopía 7 .…”
unclassified